941 Screen time: who's watching? A community paediatric survey on screen time use and management. (17th August 2022) - Rodrigues, Sarah; Banerjee, Indrani
Abstract : Aims: Screens are increasingly becoming part of everyday life and their use is likely to have increased during the recent pandemic. A recent Ofcom report found that 98% of 3 to 4 year olds watched TV or films for 12 hours a week (1). Research has indicated a range of positive and negative impacts of screen use on development, with mainly negative associations in under 2 year olds (2). The purpose of our project was to investigate current practices amongst our multidisciplinary team on asking and advising about screen time, and to find out about screen time use in our local paediatric population accessing neurodevelopmental clinics. Methods: Paper questionnaires were developed and distributed to our multidisciplinary community paediatric team to enquire about their practices around addressing screen time in clinic. Following this, paper questionnaires enquiring about children's screen time use were developed and distributed to parents of children attending outpatient community paediatric clinic appointments over a two-week period in January 2022. Questionnaires were collected and analysed anonymously. Results: 20 questionnaires were completed by community paediatric doctors and therapists. None of the participants said they routinely asked or advised about screen time. 50% said they sometimes asked and 60% sometimes advised about screen time. All participants felt that screen time could have an effect on development. 27 questionnaires were completed by parents. Age of children ranged between 3 and 13 years. All parents reported that their child used screens. Age when children started using screens ranged from 6 months to 4 years. Type of screens used included television, phone, tablet and computer. 78% of children were reported to watch children's television and 48% watched online videos. There were a range of times when children used screens ( figure 1 ). Total daily screen time ranged from under 1 hour to 5 hours, with a mean of 2 hours ( figure 2 ). 81% of parents had concerns about their child's development. One third of parents were concerned about their child's use of screen time. 29% were aware of current screen time recommendations. 41% said they would like more advice about screen time, with half saying they would like written advice and half requesting verbal advice. Conclusion: This project has provided an insight into current screen time use amongst community paediatric patients. The survey has highlighted that providing screen time advice is not routinely done in our practice at present. We were interested to find that only one third of parents were aware of current screen time recommendations. These findings prompt us to consider whether we should routinely ask and advise about screen time use during community paediatric consultations. The next step of our project will aim to provide useful information on screen time to our patients and their families. (1) Children and parents: media use and attitudes report 2019, Ofcom. (2) Paediatrics Volume 140, s2, Nov 2017, Anderson et al.